THE METHODOLOGY AND STYLE OF TAFSIR HIDAYAT-UL-QURAN BY MUFTI SAEED AHMAD PALANPURI - Muneeba Shahzadi; Dr. Mahmood Ahmad* (`, 2025)
This research paper explores the methodology and style of Tafseer Hidayat-ul-Quran by Mufti Saeed Ahmad Palanpuri, a prominent Islamic scholar and exegete. The study analyzes how Palanpuri explains Qur’anic injunctions, complex issues, and contemporary needs in a simple, fluent, and reader-friendly language while maintaining scholarly depth and textual accuracy. It highlights unique features of the tafseer, such as presenting the historical background of surahs, explaining the chronological order of revelation, providing meanings of difficult words, and clarifying grammatical structures. The paper further examines his approach of interpreting the Qur’an through the Qur’an itself, hadith, and statements of companions and tabi’un. His method reflects a balanced combination of traditional scholarship and pedagogical clarity, making the tafseer a valuable resource for both scholars and lay readers seeking Qur’anic understanding. Keywords:Tafseer Hidayat-ul-Quran, Saeed Ahmad Palanpuri, Qur’anic exegesis, methodology, style of tafseer, Qur’anic interpretation, Islamic scholarship